2000
DOI: 10.1074/jbc.275.10.6841
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Native Structure of Stathmin and Its Interaction Domains with Tubulin

Abstract: Stathmin is a cytosoluble phosphoprotein proposed to be a regulatory relay integrating diverse intracellular signaling pathway. Its interaction with tubulin modulates microtubule dynamics by destabilization of assembled microtubules or inhibition of their polymerization from free tubulin. The aim of this study was to probe the native structure of stathmin and to delineate its minimal region able to interact with tubulin. Limited proteolysis of stathmin revealed four structured domains within the native protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…18). Moreover, our result is in line with a recent report demonstrating that truncation of both the N-and C-terminal flanks of Op18 abolishes tubulin binding as determined by size exclusion chromatography (23).…”
Section: The Central ␣-Helical Part Of Op18 Contains Overlappingsupporting
confidence: 82%
“…18). Moreover, our result is in line with a recent report demonstrating that truncation of both the N-and C-terminal flanks of Op18 abolishes tubulin binding as determined by size exclusion chromatography (23).…”
Section: The Central ␣-Helical Part Of Op18 Contains Overlappingsupporting
confidence: 82%
“…1) together with deletion mapping (13,18,19,26,29,41) and mutational studies (40,42) indicate that the helical domain of stathmin accounts predominantly for the binding free energy. Interestingly, the interaction sites of the two ␣/␤-tubulin heterodimers with the RB3-SLD helix (T ␣1␤1 -S h1 and T ␣2␤2 -S h2 ; Fig.…”
Section: Mechanism Of Tubulin-stathmin Complex Formation-thementioning
confidence: 99%
“…All these studies indicated that stathmin interacts with two ␣/␤-tubulin heterodimers in the low micromolar range. In analytical ultracentrifugation (21,30) and gel filtration (18,22,32) studies only ternary (denoted T 2 S) but not binary (denoted TS) complexes were isolated. Consistent with this observation, pulldown assays using agarose bead-coupled antibodies against glutathione S-transferase-and FLAG-tagged stathmin variants suggested that the binding of tubulin to stathmin is highly cooperative and that binary TS complexes are labile intermediates (26,28,41).…”
Section: Mechanism Of Tubulin-stathmin Complex Formation-thementioning
confidence: 99%
See 1 more Smart Citation
“…Stathmin indeed interacts with two ␣ /␤ tubulin heterodimers in vitro to form a T 2 S complex (22,23). The two tubulin heterodimers bind mostly the predicted ␣-helical "interaction" domain of stathmin (24), likely forming a curved complex whose three-dimensional structure has been recently revealed with the stathmin-like domain of RB3 (25). Stathmin displays a microtubule destabilizing activity both in vitro and in vivo (21, 26 -29), which is stoichiometrically accounted for in vitro by a free tubulin sequestration mechanism (22,27), although it has been proposed to be also due in part to a direct catastrophe-promoting activity (21,30,31).…”
mentioning
confidence: 99%